2008
DOI: 10.1186/1471-2172-9-25
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10+ T cells and NK cells assist in the recruitment and activation of CXCR3+ and CXCL11+ leukocytes during Mycobacteria-enhanced colitis

Abstract: BackgroundThe role of Mycobacteria in the etiology of Crohn's disease (CD) has been a contentious subject for many years. Recently, our laboratory showed that spontaneous colitis in IL-10-/- mice is driven in part by antigens (Ags) conserved in Mycobacteria. The present study dissects some of the common cellular and molecular mechanism that drive Mycobacteria-mediated and spontaneous colitis in IL-10-/- mice.ResultsWe show that serum from inflammatory bowel disease (IBD) patients contain significantly higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…4) and that the number of these cells significantly declined in MLN and LP after resveratrol treatment. These results confirmed our earlier findings that the numbers of CD4 ϩ T cells in spleens, MLN, and LP represent the majority of lymphocytes expressing inflammatory cytokines during colitis (Singh et al, 2008a). This finding is also in agreement with the findings of other studies using DSS-induced colitis models that showed the potentiation of CD4 ϩ T cells in colitis (Dieleman et al, 1998;Shintani et al, 1998;Grose et al, 2001;Ogawa et al, 2004).…”
Section: Fig 8 Resveratrol Modulates Dss-induced Cd4supporting
confidence: 83%
“…4) and that the number of these cells significantly declined in MLN and LP after resveratrol treatment. These results confirmed our earlier findings that the numbers of CD4 ϩ T cells in spleens, MLN, and LP represent the majority of lymphocytes expressing inflammatory cytokines during colitis (Singh et al, 2008a). This finding is also in agreement with the findings of other studies using DSS-induced colitis models that showed the potentiation of CD4 ϩ T cells in colitis (Dieleman et al, 1998;Shintani et al, 1998;Grose et al, 2001;Ogawa et al, 2004).…”
Section: Fig 8 Resveratrol Modulates Dss-induced Cd4supporting
confidence: 83%
“…Deleterious effects of NK cell activation were reported after infection with both gram-negative (for example, E. coli [185] and Ehrlichia chaffensis [186]) and grampositive bacteria (for example, Streptococcus pneumoniae [187] and Streptococcus pyogenes [188]) independent of the site of infection (systemic, peritoneal or pulmonary). Most interestingly, NK cells may also contribute to adverse evolution of the infectious diseases as shown by their association with a Helicobacter pylori-dependent state of early-stage highgrade gastric mucosa-associated lymphoid tissue lymphoma (189) and Mycobacteria-mediated colitis in susceptible hosts (190). Of course and as expected, NK cells contribute to the deleterious effects seen after LPS injections (85,191).…”
Section: Benefits Versus Disadvantages Of Nk Cell Activation During Bmentioning
confidence: 67%
“…Though oxymatrine blocks LPS-induced TNFα production in both IECs and BMDCs in vitro , the in vivo source of TNFα is not clear. Intestinal myofibroblasts34 and NKT35 cells are an important source of TNFα and could be unaffected by oxymatrine exposure. In addition, it is possible that the effect of oxymatrine on NF-κB in vivo could be coupled with effects on other signaling pathways such as p38MAPK1112 and acts to balance target gene transactivation lowering pro-inflammatory effects while preserving cyto-protective ones.…”
Section: Discussionmentioning
confidence: 99%